Personality Test Disc Application Design in Android Based Business - Selvia Lorena Br Ginting; K Ezhar; R Dean; S R Faiza; M Maryati (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2021)
The purpose of making this android-based application design is to maximize the potential of each colleague who wants or is running a business. The method used to meet system development needs is the descriptive analysis method with a qualitative approach. Object-oriented development methods and prototyping development methods are used as the basis for building the system. The results show that the data information collected through the application can provide information in tips that can be applied. This system is formed based on the DISC Test personality results, which will be processed through the system. Then the match values are obtained with the predetermined business field data to obtain appropriate results. Using this application is expected to make business people more aware of each consumer's personality desires. With this application, the results of the data obtained are expected to help fellow beginner businessmen determine what position or business is suitable for them. This application acts as a helper or advisor that makes it easier for entrepreneurs to make decisions and increase the businessman's potential.